Implementasi Model Peer Teaching Dalam Pembelajaran Bulutangkis di Kelas IX SMP Negeri 4 Purwadadi - Ageng Fahrurozi Sopandi; Abduloh; Abdul Salam Hidayat (Universitas Singaperbangsa, 2021)
This study aims to describe the implementation of the peer teaching model in badminton learning in class IX of SMP Negeri 4 Purwadadi. The problem of this study is to describe how to describe the implementation of the peer teaching model in badminton learning in class IX of SMP Negeri 4 Purwadadi. This research is a case study research, which describes how the process and results of implementing the peer-teaching model in badminton learning at SMP Negeri 4 Purwadadi, the subjects in this study were 1 physical education teacher, 1 tutor student and 3 students. Data collection techniques used in this study were observation, interviews, and documentation. Data analysis techniques used in this research are data reduction and data display techniques. The results of the study stated that the process of implementing learning using the peer teaching model had been going quite well and the results of the learning using the peer teaching model in the aspect of material mastery, attitudes and practical skills were quite good as seen from the changes that occurred in students and students in class IX SMP Negeri 4 Purwadadi.